Chemically strengthened glass and its manufacturing method

The chemically strengthened glass with a controlled Na concentration and stress gradient addresses the inefficiencies of conventional two-stage processes, enhancing strength and weather resistance by suppressing tensile stress and maintaining a flat stress profile.

JP7609065B2Active Publication Date: 2025-01-07AGC INC
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021527402
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-06-26
Filing Date
2020-04-09
Publication Date
2025-01-07
Estimated Expiration
2040-04-09

AI Technical Summary

Technical Problem

Conventional two-stage chemical strengthening processes for lithium-containing glass are complex and inefficient, leading to increased internal tensile stress and a parabolic stress profile, which compromises the strength and production efficiency of chemically strengthened glass.

Method used

A chemically strengthened glass with a specific Na concentration and stress gradient, characterized by a slope of -15MPa/μm to -3MPa/μm and a monotonically decreasing Na concentration curve, suppresses tensile stress and introduces high surface compressive stress, achieving a stress profile similar to lithium-free glass.

Benefits of technology

The glass exhibits enhanced strength and weather resistance while minimizing fracture risk, maintaining a flat tensile stress profile and ensuring efficient production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609065000003
    Figure 0007609065000003
  • Figure 0007609065000004
    Figure 0007609065000004
  • Figure 0007609065000005
    Figure 0007609065000005
Patent Text Reader

Abstract

The purpose of the present invention is to provide: a lithium-containing chemically strengthened glass that has a high surface compressive stress while having a stress profile similar to that of a conventional lithium-free glass, and in which the compressive stress is introduced only in the vicinity of a surface layer thereof; and a manufacturing method therefor. The present invention relates to a chemically strengthened glass or the like having a first principal surface, a second principal surface facing the first principal surface, and an end section that is in contact with the first principal surface and the second principal surface. When a compressive stress value inside the glass is expressed with the depth from the first principal surface as a variable, (1a) the gradient of a stress curve and the gradient of an Na concentration curve are within specific ranges in the plate thickness range of (the depth at which the compressive stress value is 0) ± 10 μm; (2a) the gradient of the Na concentration curve monotonically decreases in the plate thickness range between the first principal surface and the depth at which the compressive stress value is 0; (3a) the thickness is 1 mm or less; and (4a) the content of Li2O expressed in terms of oxide by molar percentage is 10 mol% or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to chemically strengthened glass and a method for producing the same. [Background technology]

[0002] 2. Description of the Related Art Cover glass made of chemically strengthened glass is used for the purpose of protecting display devices such as mobile phones, smartphones, and tablet terminals and enhancing their aesthetic appearance.

[0003] In chemically strengthened glass, the strength tends to increase as the surface compressive stress (value) (CS) and depth of compressive stress layer (DOL) increase. On the other hand, internal tensile stress (value) (CT) occurs inside the glass to maintain a balance with the compressive stress of the glass surface, so the CT increases as CS and DOL increase. Glass with a large CT will have an explosive increase in the number of fractures when damaged, increasing the risk of fragments scattering.

[0004] Patent Document 1 describes that two-stage chemical strengthening can increase surface compressive stress while suppressing internal tensile stress. Specifically, it discloses a method in which a KNO3 / NaNO3 mixed salt with a low K concentration is used for the first stage of chemical strengthening, and a KNO3 / NaNO3 mixed salt with a high K concentration is used for the second stage of chemical strengthening.

[0005] Patent Document 2 discloses lithium-containing glass having a relatively large surface compressive stress and compressive stress layer depth due to two-stage chemical strengthening. The lithium-containing glass can increase both CS and DOL while suppressing CT by a two-stage chemical strengthening treatment using a sodium salt in the first stage and a potassium salt in the second stage.

[0006] Patent Document 3 describes a glass article containing a metal oxide concentration gradient and discloses the chemical strengthening stress profile of a conventional lithium-free glass (Patent Document 3, FIG. 2). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] US Patent Application Publication No. 2015 / 0259244 [Patent Document 2] Japan Special Publication No. 2013-520388 [Patent Document 3] Japanese Patent Application Publication No. 2019-510726 Summary of the Invention [Problem to be solved by the invention]

[0008] The stress profile of conventional lithium-free chemically strengthened glass is shown in Figure 1, and the stress profile of conventional lithium-containing chemically strengthened glass is shown in Figure 2. When chemically strengthening lithium-containing glass, the diffusion rate of lithium is fast and stress relaxation occurs, so ion exchange is required deep in the plate thickness direction to increase the surface compressive stress. Therefore, when conventional lithium-containing glass is chemically strengthened, the stress profile becomes parabolic as shown in Figure 2, and tensile stress tends to increase along with the surface compressive stress. In addition, there is a problem that Na-Li exchange occurs substantially to the center of the plate thickness.

[0009] Conventionally, two-stage chemical strengthening has been used to solve these problems, but two-stage chemical strengthening is complicated and has problems in terms of production efficiency.In addition, when the lithium content (Li2O content) in lithium-containing glass is high (e.g., 10 mol% or more on an oxide basis) in terms of mole percentage on an oxide basis, the stress profile of the chemically strengthened glass becomes parabolic, and the tendency for the tensile stress to increase is particularly pronounced, so it is necessary to effectively increase the compressive stress.

[0010] In view of this situation, the present invention provides a lithium-containing chemically strengthened glass having a stress profile similar to that of conventional lithium-free glass, a high surface compressive stress, and a compressive stress introduced only near the surface layer. An object of the present invention is to provide a method for producing the same. [Means for solving the problem]

[0011] As a result of studying the above problems, the present inventors have found that in a chemically strengthened glass containing 10 mol% or more of Li2O, the ductility of the glass surface can be increased and the strength can be improved by adjusting the Na concentration gradient and the stress gradient. Based on these findings, the present invention has been completed.

[0012] That is, the present invention is as follows. 1. A semiconductor device having a first main surface, a second main surface opposite to the first main surface, and an end portion in contact with the first main surface and the second main surface; When the compressive stress value inside the glass is expressed using the depth from the first main surface as a variable, Chemically strengthened glass that satisfies the following (1a) to (4a). (1a) In the thickness range of ±10 μm at a depth where the compressive stress value is 0, The gradient of the stress curve is -15MPa / μm to -3MPa / μm, and The gradient of the Na concentration curve defined below has an absolute value of 0.02 / μm to 0.12 / μm. Na concentration curve: A Na concentration curve obtained by converting the Na ion concentration profile in the sheet thickness direction of the chemically strengthened glass measured by EPMA into an oxide-based molar percentage. (2a) The gradient of the Na concentration curve in the thickness direction range between the first principal surface and the depth at which the compressive stress value is 0 monotonically decreases. (3a) The thickness is 1 mm or less. (4a) Contains 10 mol% or more of Li2O, expressed as mole percentage on an oxide basis. 2. The chemically strengthened glass according to claim 1, wherein the thickness is t (μm), and the average value of the gradient of the stress curve in the thickness direction range between the thickness center tc (μm) and (tc-0.20×t) (μm) has an absolute value of less than 1 MPa / μm. 3. In the range in the plate thickness direction between the first main surface and the depth where the compressive stress value is 0, The compressive stress curve measured using the birefringence imaging system Abrio-IM manufactured by Tokyo Instruments Inc. includes an inflection point, and 3. The chemically strengthened glass according to 1 or 2, wherein the Na concentration curve does not include an inflection point. 4. The chemically strengthened glass according to claim 3, wherein the compressive stress curve includes an inflection point in the range in the plate thickness direction between a position at a depth of 10 μm from the first main surface and a depth at which the compressive stress value is 0. 5. The chemically strengthened glass according to any one of 1 to 4 above, which is glass-ceramic. 6. The chemically strengthened glass according to 5 above, wherein the crystallization rate of the crystallized glass is 10% or more. 7. The chemically strengthened glass according to 5 or 6, wherein the crystallized glass contains lithium metasilicate crystals. 8. The chemically strengthened glass according to any one of 5 to 7 above, having a haze value of transmitted light converted to a thickness of 0.7 mm, measured by a method in accordance with JIS K 7136 (2000), of 0.01 to 0.2%. 9. The chemically strengthened glass according to any one of 5 to 8 above, having a visible light transmittance converted to a thickness of 0.7 mm of 85% or more. 10. A method for producing chemically strengthened glass, comprising chemically strengthening glass having a first main surface, a second main surface opposite to the first main surface, and an end portion in contact with the first main surface and the second main surface, a thickness of 1 mm or less, and containing 10 mol% or more of Li2O expressed as a mole percentage based on oxides, The chemical strengthening is performed using a strengthening salt containing sodium and having a potassium content of less than 5% by mass, The obtained chemically strengthened glass has a compressive stress value inside the glass expressed as a variable of the depth from the first main surface, A method for producing chemically strengthened glass, which satisfies the following (1b) and (2b). (1b) In the thickness range of ±10 μm at a depth where the compressive stress value is 0, The gradient of the stress curve is -15MPa / μm to -3MPa / μm, and The gradient of the Na concentration curve defined below has an absolute value of 0.02 / μm to 0.12 / μm. Na concentration curve: A Na concentration curve obtained by converting the Na ion concentration profile in the sheet thickness direction of the chemically strengthened glass measured by EPMA into an oxide-based molar percentage. (2b) The gradient of the Na concentration curve in the thickness direction range between the first principal surface and the depth at which the compressive stress value is 0 monotonically decreases. 11. The method for producing chemically strengthened glass according to claim 10, wherein the glass is crystallized glass. 12. The crystallized glass is In terms of mole percentage based on oxide, SiO2 40-65%, Al2O3 0-10%, Li2O 20~40%, Na2O 0-10%, K2O 0.1-10%, 12. The method for producing chemically strengthened glass according to claim 11, 13. The method for producing chemically strengthened glass according to claim 11 or 12, wherein the crystallized glass has a visible light transmittance of 85% or more when converted to a thickness of 0.7 mm. 14. The method for producing chemically strengthened glass according to any one of 11 to 13, wherein the crystallized glass contains lithium metasilicate crystals. Effect of the Invention

[0013] The chemically strengthened glass of the present invention has a Na concentration gradient and a stress gradient within specific ranges, and while containing 10 mol% or more of LiO on an oxide basis, it has a stress profile similar to that of conventional lithium-free glass, is inhibited from fracturing when scratched, and exhibits excellent strength and weather resistance. [Brief description of the drawings]

[0014] [Figure 1] FIG. 1 is a diagram showing an example of a stress profile of a conventional lithium-free chemically strengthened glass. [Diagram 2] FIG. 2 is a diagram showing an example of a stress profile of conventional lithium-containing chemically strengthened glass. [Diagram 3]FIG. 3 is a diagram showing one embodiment of a stress profile of the chemically strengthened glass of the present invention. [Figure 4] 4(a) and (b) are diagrams showing an embodiment of the ion concentration profile of the chemically strengthened glass of the present invention. Fig. 4(a) is a diagram showing the signal intensity of main ions in Example 1, and Fig. 4(b) is a diagram showing the calculated Na ion concentration profile. [Diagram 5] 5(a) and (b) are schematic diagrams showing how to prepare a sample for measuring the surface compressive stress (CS) of chemically strengthened glass. Fig. 5(a) shows the sample before polishing, and Fig. 5(b) shows the thin-sectioned sample after polishing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The chemically strengthened glass of the present invention will be described in detail below, but the present invention is not limited to the following embodiments, and can be arbitrarily modified and implemented within the scope of the present invention.

[0016] In this specification, "chemically strengthened glass" refers to glass after chemical strengthening treatment. Moreover, "glass for chemical strengthening" refers to glass before chemical strengthening treatment.

[0017] In this specification, the glass composition of the chemically strengthened glass may be referred to as the base composition of the chemically strengthened glass. In chemically strengthened glass, a compressive stress layer is usually formed on the glass surface due to ion exchange, so the glass composition of the non-ion-exchanged portion coincides with the base composition of the chemically strengthened glass. In addition, the concentration of components other than alkali metal oxides does not basically change even in the ion-exchanged portion.

[0018] In this specification, the glass composition is expressed in mole percentage based on oxides, and mole % may be simply written as %. Furthermore, the symbol "~" indicating a numerical range is used to mean that the numerical values ​​before and after it are included as the lower and upper limits.

[0019] In the glass composition, the term "substantially free" means that it is not contained except for unavoidable impurities contained in raw materials, etc., that is, it is not intentionally contained. For example, the content in the glass composition is less than 0.1 mol % except for transition metal oxides that cause coloring.

[0020] In this specification, the term "stress profile" refers to a pattern that expresses compressive stress values ​​with the depth from the glass surface as a variable. A negative compressive stress value means tensile stress. The "depth of compressive stress layer (DOC)" is the depth at which the compressive stress value (CS) is 0. The "internal tensile stress value (CT)" refers to the tensile stress value at a depth of 1 / 2 the glass sheet thickness t.

[0021] Generally, the stress profile is often measured using an optical waveguide surface stress meter (e.g., FSM-6000 manufactured by Orihara Seisakusho). However, due to the measurement principle, the optical waveguide surface stress meter cannot measure stress unless the refractive index decreases from the surface toward the inside. As a result, when lithium aluminosilicate glass is chemically strengthened with sodium salt, compressive stress cannot be measured. Therefore, in this specification, the stress profile is mainly measured using a scattered light photoelastic stress meter (e.g., SLP-1000 manufactured by Orihara Seisakusho). The scattered light photoelastic stress meter can measure the stress value regardless of the refractive index distribution inside the glass. However, since the scattered light photoelastic stress meter is easily affected by the surface scattered light, it is difficult to accurately measure the stress value near the glass surface. For the surface layer part up to a depth of 10 μm from the surface, the stress value can also be estimated by a method of extrapolation using a complementary error function based on the measurement value of the deeper part. Alternatively, the birefringence can be measured using a sliced ​​sample as described below, for example, using a birefringence imaging system Abrio-IM manufactured by Tokyo Instruments Inc.

[0022] 1. Chemically strengthened glass The chemically strengthened glass of the present invention has a first main surface, a second main surface opposite to the first main surface, and an end portion in contact with the first main surface and the second main surface, When the compressive stress value inside the glass is expressed using the depth from the first main surface as a variable, A chemically strengthened glass sheet that satisfies the following (1) to (4). (1) In the thickness direction range of ±10 μm, where the compressive stress value is 0, The gradient of the stress curve is -15MPa / μm to -3MPa / μm, and The gradient of the Na concentration curve defined below has an absolute value of 0.02 / μm to 0.12 / μm. Na concentration curve: a Na concentration curve obtained by converting the Na ion concentration profile in the plate thickness direction of the chemically strengthened glass plate measured by EPMA into an oxide-based molar percentage. (2) The gradient of the Na concentration curve in the thickness direction range between the first principal surface and the depth at which the compressive stress value is 0 monotonically decreases. (3) The thickness is 1 mm or less. (4) Contains 10 mol% or more of Li2O, expressed as mole percentage on an oxide basis.

[0023] <Stress profile and Na concentration profile> Fig. 3 is a diagram showing one embodiment of the stress profile of the chemically strengthened glass of the present invention. The stress profile shown in Fig. 3 shows a profile on one of the main surfaces. In the present invention, the stress profiles of one main surface and the other main surface may be the same or different. Figs. 4(a) and (b) are diagrams showing one embodiment of the ion concentration profile of the chemically strengthened glass of the present invention.

[0024] The chemically strengthened glass of the present invention has a gradient of a stress curve of -15 MPa / μm to -3 MPa / μm in the thickness direction within a range of ±10 μm at a depth where the compressive stress value is 0, and has an absolute value of a gradient of a Na concentration curve of 0.02 / μm to 0.12 / μm.

[0025] In the present invention, the "Na concentration curve" refers to a Na concentration curve obtained by converting the Na ion concentration profile in the plate thickness direction of the chemically strengthened glass plate measured by EPMA (electron probe micro analyzer) into an oxide-based molar percentage.

[0026] In the stress profile, the depth where the compressive stress value is zero represents the depth of the compressive stress layer (DOL). The DOL of chemically strengthened glass can be appropriately adjusted by adjusting the chemical strengthening conditions, the glass composition, etc. The DOL of the chemically strengthened glass of the present invention is the depth from the glass surface to the part where the stress becomes zero in the stress profile, and is a value measured using a scattered light photoelastic stress meter (for example, SLP-1000 manufactured by Orihara Seisakusho). It can also be measured using a thin-sectioned sample as described later using a birefringence imaging system Abrio-IM manufactured by Tokyo Instruments Co., Ltd.

[0027] The chemically strengthened glass of the present invention has a gradient of a stress curve of -15 MPa / μm to -3 MPa / μm, preferably -13 MPa / μm to -3.5 MPa / μm, and more preferably -11 MPa / μm to -4 MPa / μm in the thickness direction range of a depth of ±10 μm where the compressive stress value is 0. By having a gradient of -15 MPa / μm to -3 MPa / μm in the thickness direction range of a depth of ±10 μm where the compressive stress value is 0, the energy caused by the concentration gradient is suppressed from dissipating and can be effectively converted into stress, so that sufficient surface compressive stress is obtained and excellent strength is exhibited.

[0028] The chemically strengthened glass of the present invention has an absolute gradient of 0.02 / μm to 0.12 / μm, preferably 0.03 / μm to 0.11 / μm, and more preferably 0.04 / μm to 0.10 / μm, of a Na concentration curve in a thickness direction range of ±10 μm to a depth where the compressive stress value is 0. By having an absolute gradient of 0.02 / μm to 0.12 / μm of a Na concentration curve in a thickness direction range of ±10 μm to a depth where the compressive stress value is 0, an increase in tensile stress can be suppressed.

[0029] In the chemically strengthened glass of the present invention, the gradient of the Na concentration curve in the range in the sheet thickness direction between the first main surface and the depth where the compressive stress value is 0 is monotonically decreasing. The monotonically decreasing gradient of the Na concentration curve in this range can suppress an increase in tensile stress and suppress fracture during scratching. In the present invention, "the gradient of the Na concentration curve is monotonically decreasing" means that the gradient of the Na concentration curve has a non-zero negative inclination from the glass surface toward the inside of the glass at any point in the range.

[0030] In one embodiment, the chemically strengthened glass of the present invention has a value obtained by dividing the gradient of the stress curve by the gradient of the Na concentration curve in the thickness direction range of a depth of ±10 μm where the compressive stress value is 0, of preferably 80 to 200, more preferably 90 to 180, and even more preferably 100 to 150. By dividing the gradient of the stress curve by the gradient of the Na concentration curve in the thickness direction range of a depth of ±10 μm where the compressive stress value is 0, of 80 to 200, dissipation of energy caused by the concentration gradient is further suppressed and can be effectively converted into stress, so that the glass exhibits sufficient surface compressive stress, suppresses an increase in tensile stress, and suppresses fracture when scratched.

[0031] In one embodiment, the chemically strengthened glass of the present invention has a thickness of t (μm) and a thickness center of tc (μm). In the thickness direction range between the thickness center tc (μm) and (tc-0.20×t) (μm), the average absolute value of the gradient of the stress curve is preferably less than 1 MPa / μm, more preferably 0.9 MPa / μm or less, and even more preferably 0.8 MPa / μm or less. By having the average absolute value of the gradient of the stress curve be less than 1 MPa / μm, the glass has a substantially flat tensile stress profile, similar to the conventional lithium-free chemically strengthened glass shown in FIG. 1, and the surface compressive stress can be increased while suppressing the internal tensile stress.

[0032] In addition, the absolute value of the gradient of the stress curve at each point in the thickness range of tc±0.20t (μm) is preferably less than 1 MPa / μm, more preferably 0.9 MPa / μm or less, and even more preferably 0.8 MPa / μm or less. By having the absolute value of the gradient of the stress curve be less than 1 MPa / μm, a substantially flat stress profile is obtained over a wider range of the tensile stress region, and the surface compression region can be enlarged while suppressing the internal tensile stress.

[0033] In one embodiment, in the chemically strengthened glass of the present invention, in the range in the plate thickness direction between the first main surface and the depth at which the compressive stress value is 0, the compressive stress curve measured using a birefringence imaging system Abrio-IM manufactured by Tokyo Instruments Inc. It is preferable that the curve does not include an inflection point, and the Na concentration curve does not include an inflection point.

[0034] Measurement of compressive stress using the birefringence imaging system Abrio-IM manufactured by Tokyo Instruments Inc. is performed according to the following procedure. Figures 5(a) and (b) are schematic diagrams showing how to prepare a sample for measuring the surface compressive stress (CS) of chemically strengthened glass. Figure 5(a) shows the sample before polishing, and Figure 5(b) shows the thinned sample after polishing. As shown in Figure 5(b), a cross section of chemically strengthened glass with a size of 10 mm x 10 mm or more and a thickness of about 0.2 to 2 mm is polished to a thickness of 150 to 750 μm and thinned.

[0035] The polishing procedure involves grinding to the target thickness plus 50 μm using a #1000 diamond electroplated grinding wheel, then grinding to the target thickness plus 10 μm using a #2000 diamond electroplated grinding wheel, and finally mirror finishing with cerium oxide to reach the target thickness. For the sample thinned to about 200 μm as described above, measurements were performed using transmitted light using monochromatic light with λ = 546 nm as a light source, and the phase difference (retardation) of the chemically strengthened glass was measured using a birefringence imaging system, and the stress was calculated using the obtained value and the following formula (1). F=δ / (C×t')...Equation (1) In equation (1), F is stress (MPa), δ is phase difference (retardation) (nm), and C is the photoelastic constant (nm cm -1 MPa), and t' is the sample thickness (cm).

[0036] In the present invention, the "inflection point" refers to a point where the second derivative of the curve becomes zero. In other words, it refers to a point where the sign of the curvature of the curve changes. Note that, when calculating the derivative, it is preferable to reduce the measurement noise by smoothing or the like before performing the calculation. For example, preprocessing can be performed using the known Savitzky-Golay method.

[0037] When a glass plate is bent by an impact, if the amount of bending is large, a large tensile stress is applied to the glass surface, causing the glass to break. In this specification, such breakage is referred to as "glass breakage due to bending mode."

[0038] In the range in the sheet thickness direction between the first main surface and the depth where the compressive stress value is 0, the compressive stress curve includes an inflection point, and the Na concentration curve does not include an inflection point, so that the stress tends to relax while the concentration gradient is maintained, particularly on the glass sheet surface. That is, it shows that the surplus of the energy caused by the concentration gradient is dissipated sufficiently and necessary. Therefore, it is possible to suppress glass breakage due to bending mode while introducing a sufficient amount of compressive stress to the glass surface, and to suppress deterioration of weather resistance. From the viewpoint of further improving the strength, in one aspect, the chemically strengthened glass of the present invention preferably includes an inflection point in the compressive stress curve in the range in the sheet thickness direction between the position at a depth of 10 μm from the first main surface and the depth where the compressive stress value is 0.

[0039] In the past, when creating such a stress curve in lithium-free glass, annealing or the like was performed after ion exchange to relax the concentration gradient. However, this relaxes the energy itself caused by the concentration gradient, so the stress is relaxed excessively, resulting in significant deterioration of the surface stress. In addition, in glasses containing 10 mol% or more Li2O, the ion diffusion rate is high as mentioned above, and there was no known method of introducing stress until stress relaxation occurs over a relatively wide area of ​​the surface, especially near the surface.

[0040] The chemically strengthened glass of the present invention is manufactured by subjecting lithium aluminosilicate glass to an ion exchange treatment. Compared with sodium aluminosilicate glass, which has been widely used as a chemically strengthened glass, lithium aluminosilicate glass has a large fracture toughness value and tends to be less likely to break even if scratched. In addition, even if the compressive stress value of the glass surface is increased, severe shattering tends to be less likely to occur.

[0041] In one embodiment, the chemically strengthened glass of the present invention has a CSO of preferably 500 MPa or more, more preferably 550 MPa or more, and even more preferably 600 MPa or more. By having a CSO of 500 MPa or more, the tensile stress caused by dropping is offset, making the glass less likely to break, and fracture due to bending mode can be suppressed. In addition, the total amount of compressive stress in the glass surface layer is constant, and if CSO is too high, the CS, which is the CS inside the glass, is increased. 50 Therefore, from the viewpoint of preventing crushing upon impact, CSO is preferably 1000 MPa or less, more preferably 950 MPa or less, and further preferably 900 MPa or less.

[0042] In one embodiment, the chemically strengthened glass of the present invention is 50 is preferably 150 MPa or more, more preferably 170 MPa or more, and further preferably 180 MPa or more. 50 By setting the CS to 150 MPa or more, the strength can be improved. 50If CS is too high, the internal tensile stress CT increases and the material becomes more susceptible to fracture. 50 It is preferably 250 MPa or less, more preferably 240 MPa or less, and further preferably 230 MPa or less.

[0043] If the depth (DOL) at which the compressive stress value is 0 is too large relative to the thickness t [unit: μm], it will lead to an increase in CT, so it is preferably 0.2t or less, more preferably 0.19t or less, and even more preferably 0.18t or less. Specifically, for example, when the plate thickness t is 0.8 mm, it is preferably 160 μm or less. In addition, from the viewpoint of improving strength, it is preferably 0.06t or more, more preferably 0.08t or more, even more preferably 0.10t or more, and particularly preferably 0.12t or more.

[0044] Glass with a large fracture toughness value has a large CT limit, so even if a large surface compressive stress is introduced into the glass by chemical strengthening, severe fracture is unlikely to occur. From the viewpoint of suppressing fracture when scratched, in one embodiment of the chemically strengthened glass of the present invention, the fracture toughness value of the mother glass is 0.8 MPa m 1 / 2 It is preferable that the viscosity is equal to or higher than 0.85 MPa m. 1 / 2 More preferably, 0.9 MPa m 1 / 2 The fracture toughness value is usually 2.0 MPa m 1 / 2 Typically, it is 1.5 MPa m 1 / 2 The following is the result.

[0045] The fracture toughness value can be measured, for example, by using the DCDC method (Acta metall. mater. Vol.43: p. 3453-3458, 1995). The fracture toughness value can be simply evaluated by the indentation method. The method of making the fracture toughness value within the above range includes, for example, a method of adjusting the crystallization condition (time and temperature of heat treatment), glass composition, cooling rate, etc. of the crystallized glass to adjust the crystallization rate, fictive temperature, etc. Specifically, for example, in the case of crystallized glass, the crystallization rate of the crystallized glass described later is preferably 15% or more, more preferably 18% or more, and even more preferably 20% or more. In addition, the crystallization rate of the crystallized glass is preferably 60% or less, more preferably 55% or less, and even more preferably 50% or less in order to ensure transmittance.

[0046] The weather resistance of chemically strengthened glass can be evaluated by a weather resistance test. The chemically strengthened glass of the present invention preferably has a change in haze value before and after standing at 80% humidity and 80°C for 120 hours of 5% or less (i.e., |haze value after test [%]-haze value before test [%]|≦5), more preferably 4% or less, and even more preferably 3% or less. The haze value is measured using a haze meter by a method conforming to JIS K7136 (2000).

[0047] The shape of the chemically strengthened glass of the present invention may be a shape other than a plate shape depending on the product to which it is applied, the purpose, etc. The glass plate may have a border shape with a different thickness on the periphery. The shape of the glass plate is not limited thereto, and for example, the two main surfaces may not be parallel to each other, and one or both of the two main surfaces may be entirely or partially curved. More specifically, the glass plate may be, for example, a flat glass plate without warping, or a curved glass plate having a curved surface.

[0048] The chemically strengthened glass of the present invention can be used as a cover glass for mobile electronic devices such as mobile phones, smartphones, personal digital assistants (PDAs), and tablet terminals. It is also useful as a cover glass for electronic devices such as televisions (TVs), personal computers (PCs), and touch panels that are not intended to be portable. It is also useful as a building material such as window glass, a tabletop, the interior of automobiles and airplanes, and the like, and as a cover glass for these.

[0049] The chemically strengthened glass of the present invention can be bent or molded into a shape other than a flat plate before or after chemical strengthening, and is therefore useful for applications such as housings having curved surfaces.

[0050] <Thickness> The thickness (t) of the chemically strengthened glass of the present invention is 1 mm or less, preferably 0.9 mm or less, more preferably 0.8 mm or less, and particularly preferably 0.7 mm or less. In order to obtain sufficient strength, the thickness is, for example, 0.1 mm or more, preferably 0.2 mm or more, more preferably 0.4 mm or more, and even more preferably 0.5 mm or more.

[0051] <Lithium-containing glass> The chemically strengthened glass of the present invention contains 10 mol% or more of Li2O in terms of mole percentage based on oxide. Li2O is a component that forms surface compressive stress by ion exchange and is essential. The content of Li2O is preferably 15 mol% or more, more preferably 20 mol% or more, and even more preferably 25 mol% or more. On the other hand, in order to maintain chemical durability, the content of Li2O is preferably 50 mol% or less, more preferably 45 mol% or less, and even more preferably 40 mol% or less.

[0052] The chemically strengthened glass of the present invention is a lithium-containing glass, preferably a lithium aluminosilicate glass. The lithium aluminosilicate glass is not particularly limited in form as long as it contains SiO2, Al2O3 and Li2O, but examples thereof include crystallized glass and amorphous glass. Since the fracture toughness can be increased, the crystallized glass is preferable. The crystallized glass and amorphous glass will be described below.

[0053] <<Glass-ceramics>> In the case where the lithium-containing glass in the present invention is a crystallized glass, in one embodiment, the lithium-containing glass is expressed in mole percentage based on oxides. SiO2 40-65%, Al2O3 0-10%, Li2O 20~40%, Na2O 0-10%, K2O 0-10%, It is preferable that it contains.

[0054] Crystallized glass is obtained by heat-treating and crystallizing amorphous glass, which will be described later. The glass composition of the crystallized glass is the same as that of the amorphous glass before crystallization, and will be described in the section on amorphous glass, which will be described later.

[0055] The total light visible light transmittance of the crystallized glass, including diffuse transmitted light, is preferably 85% or more when converted to a thickness of 0.7 mm, so that when used as a cover glass for a mobile display, the display screen is easy to see. The total light visible light transmittance is more preferably 88% or more, and even more preferably 90% or more. The higher the total light visible light transmittance, the more preferable it is, but it is usually 91% or less. The total light visible light transmittance of ordinary amorphous glass is about 90%. The following conversion is made to 0.7 mm.

[0056] If the total light transmittance of a crystallized glass with a thickness of t [mm] is 100×T [%] and the surface reflectance of one side is 100×R [%], then by applying the Lambert-Beer law and using the constant α, T = (1-R)2 ×exp(―αt). From here, if α is expressed in terms of R, T, and t, and t = 0.7 mm, R does not change depending on the plate thickness, so the total light transmittance T converted to 0.7 mm is 0.7 teeth T 0.7 =100×T 0.7 / t / (1-R)^(1.4 / t-2)[%] However, X^Y is X Y Represents. The surface reflectance may be calculated from the refractive index or may be actually measured. In addition, in the case of glass having a sheet thickness t of more than 0.7 mm, the sheet thickness may be adjusted to 0.7 mm by polishing, etching, or the like, and then the actual measurement may be performed.

[0057] In addition, the transmission haze value, when converted to a thickness of 0.7 mm, is preferably 1.0% or less, more preferably 0.4% or less, even more preferably 0.3% or less, particularly preferably 0.2% or less, and most preferably 0.15% or less. The smaller the transmission haze value, the better, but if the crystallization rate or the crystal grain size is reduced in order to reduce the transmission haze value, the mechanical strength decreases. In order to increase the mechanical strength, the transmission haze value in the case of a thickness of 0.7 mm is preferably 0.02% or more, more preferably 0.03% or more. The transmission haze value is a value measured by a method conforming to JIS K7136 (2000). The haze value converted to 0.7 mm can be obtained as follows.

[0058] If the total light visible transmittance of crystallized glass with a thickness of t [mm] is 100×T [%] and the transmitted haze is 100×H [%], then using the constant α used above, dH / dt ∝ exp(-αt) × (1-H) In other words, it can be considered that the transmission haze increases in proportion to the internal linear transmittance with each increase in plate thickness. This is integrated to obtain the 0.7 mm equivalent transmission haze H 0.7 teeth, H 0.7 =100×[1-(1-H)^{((1-R) 2 -T0.7 ) / ((1-R) 2 -T)}][%] However, "X^Y" is not "X Y " represents. In addition, in the case of glass having a sheet thickness t of more than 0.7 mm, the sheet thickness may be adjusted to 0.7 mm by polishing, etching, or the like, and then the actual measurement may be performed.

[0059] The Y value in the XYZ color system calculated from the total light transmission spectrum including diffuse transmission of the crystallized glass is preferably 87 or more, more preferably 88 or more, even more preferably 89 or more, and particularly preferably 90 or more. When used as the cover glass of a mobile display, it is preferable that the coloring of the glass itself is suppressed as much as possible in order to improve the reproducibility of the displayed color when used on the display screen side, and to maintain the design when used on the housing side. Therefore, the excitation purity Pe of the crystallized glass is preferably 1.0 or less, more preferably 0.75 or less, even more preferably 0.5 or less, particularly preferably 0.35 or less, and most preferably 0.25 or less.

[0060] When tempered glass made of crystallized glass is used as the cover glass of a mobile display, it is preferable that the tempered glass has a texture and a high-quality feel different from that of plastic. Therefore, the dominant wavelength λd of the crystallized glass is preferably 580 nm or less, and the refractive index is preferably 1.52 or more, more preferably 1.55 or more, and even more preferably 1.57 or more.

[0061] The crystallized glass is preferably a crystallized glass containing lithium metasilicate crystals. Lithium metasilicate crystals are expressed as Li2SiO3, and generally have diffraction peaks at Bragg angles (2θ) of 26.98°±0.2, 18.88°±0.2, and 33.05°±0.2 in a powder X-ray diffraction spectrum.

[0062] Glass-ceramics containing lithium metasilicate crystals have a higher fracture toughness value than general amorphous glass, and are less likely to break violently even when a large compressive stress is applied by chemical strengthening. In amorphous glass in which lithium metasilicate crystals can precipitate, lithium disilicate may precipitate depending on the heat treatment conditions, etc.

[0063] Lithium disilicate is expressed as Li2Si2O5, and is generally a crystal that exhibits diffraction peaks at Bragg angles (2θ) of 24.89°±0.2, 23.85°±0.2, and 24.40°±0.2 in a powder X-ray diffraction spectrum. When lithium disilicate crystals are contained, it is preferable that the lithium disilicate crystal particle size calculated from the X-ray diffraction peak width by the Scherrer formula is 45 nm or less, since transparency is easily obtained, and 40 nm or less is more preferable. Note that the Scherrer formula has a shape factor, but in this case it may be represented by the dimensionless 0.9.

[0064] However, when lithium metasilicate crystals and lithium disilicate crystals are simultaneously contained in the crystallized glass, the transparency of the crystallized glass is likely to decrease, so it is preferable that the crystallized glass does not contain lithium disilicate. Here, "does not contain lithium disilicate" means that no diffraction peak of lithium disilicate crystals is detected in the X-ray diffraction spectrum.

[0065] The crystallization rate of the crystallized glass is preferably 5% or more, more preferably 10% or more, even more preferably 15% or more, and particularly preferably 20% or more in order to increase the mechanical strength. In order to increase the transparency, it is preferably 70% or less, more preferably 60% or less, and particularly preferably 50% or less. A small crystallization rate is also excellent in that it is easy to bend and mold by heating.

[0066] The crystallinity can be calculated from the X-ray diffraction intensity by the Rietveld method. The Rietveld method is described in the "Crystal Analysis Handbook" (Kyoritsu Shuppan, 1999, pp. 492-499), edited by the Editorial Committee of the "Crystal Analysis Handbook" of the Japanese Crystallographic Society.

[0067] The average particle size of the precipitated crystals of the crystallized glass is preferably 80 nm or less, more preferably 60 nm or less, even more preferably 50 nm or less, particularly preferably 40 nm or less, and most preferably 30 nm or less. The average particle size of the precipitated crystals is determined from a transmission electron microscope (TEM) image. The average particle size of the precipitated crystals can be estimated from a scanning electron microscope (SEM) image.

[0068] The average thermal expansion coefficient of crystallized glass at 50℃ to 350℃ is 90×10 -7 / °C or more, and more preferably 100×10 -7 / °C or higher, and more preferably 110×10 -7 / °C or more, and particularly preferably 120×10 -7 / ℃ or more, most preferably 130×10 -7 / ℃ or higher.

[0069] If the thermal expansion coefficient is too large, cracks may occur due to the difference in the thermal expansion coefficient during the chemical strengthening process. Therefore, it is preferable to set the thermal expansion coefficient at 160×10 ―7 / ℃ or less, more preferably 150×10 -7 / ℃ or less, more preferably 140×10 -7 / ° C. or less. Furthermore, such a thermal expansion coefficient makes the substrate suitable for use as a support substrate for semiconductor packages that contain a large amount of resin components.

[0070] Since crystallized glass contains crystals, it has high hardness. Therefore, it is difficult to scratch and has excellent abrasion resistance. In order to increase abrasion resistance, the Vickers hardness is preferably 600 or more, more preferably 700 or more, even more preferably 730 or more, particularly preferably 750 or more, and most preferably 780 or more. If the hardness is too high, it becomes difficult to process, so the Vickers hardness of crystallized glass is preferably 1100 or less, more preferably 1050 or less, and even more preferably 1000 or less.

[0071] The Young's modulus of the crystallized glass is preferably 85 GPa or more, more preferably 90 GPa or more, even more preferably 95 GPa or more, and particularly preferably 100 GPa or more, in order to suppress warpage caused by strengthening during chemical strengthening. The crystallized glass may be polished before use. In order to facilitate polishing, the Young's modulus is preferably 130 GPa or less, more preferably 125 GPa or less, and even more preferably 120 GPa or less.

[0072] The fracture toughness value of the crystallized glass is preferably 0.8 MPa m 1 / 2 More preferably, 0.85 MPa m 1 / 2 More preferably, 0.9 MPa m 1 / 2 If the thickness is more than this, then when chemically strengthened, fragments are less likely to scatter when broken, which is preferable.

[0073] In the case where the lithium aluminosilicate glass in the present invention is a crystallized glass, it is preferable that the glass contains, in terms of mole percentage based on oxides, 40 to 60% SiO2, 0.5 to 10% Al2O3, 10 to 50% Li2O, 0 to 4% P2O5, 0 to 6% ZrO2, 0 to 7% Na2O, and 0 to 5% K2O. In other words, it is preferable to heat-treat and crystallize amorphous glass (hereinafter sometimes referred to as crystalline amorphous glass) containing, in terms of mole percentage based on oxides, 40 to 60% SiO2, 0.5 to 10% Al2O3, 15 to 50% Li2O, 0 to 4% P2O5, 0 to 6% ZrO2, 0 to 7% Na2O, and 0 to 5% K2O.

[0074] <<Crystalline amorphous glass>> In one embodiment, the amorphous glass of the present invention preferably contains, expressed as mole percentages based on oxides, 40 to 60% SiO2, 0.5 to 10% Al2O3, 10 to 50% Li2O, 0 to 4% P2O5, 0 to 6% ZrO2, 0 to 7% Na2O, and 0 to 5% K2O. The glass composition will be described below.

[0075] In crystalline amorphous glass, SiO2 is a component that forms the network structure of glass. It is also a component that increases chemical durability and is a component of lithium metasilicate, which is a precipitated crystal. The SiO2 content is preferably 40% or more. The SiO2 content is more preferably 42% or more, and even more preferably 45% or more. In order to sufficiently increase the stress due to chemical strengthening, the SiO2 content is preferably 60% or less, more preferably 58% or less, and even more preferably 55% or less.

[0076] Al2O3 is a component that increases the surface compressive stress due to chemical strengthening, and is essential. The content of Al2O3 is preferably 0.5% or more. In order to increase the stress due to chemical strengthening, the content of Al2O3 is more preferably 1% or more, and even more preferably 2% or more. On the other hand, in order to reduce the transmission haze value of the crystallized glass, the content of Al2O3 is preferably 10% or less, more preferably 8% or less, and even more preferably 6% or less.

[0077] Li2O is a component that forms surface compressive stress by ion exchange, and is a constituent of lithium silicate crystals, lithium aluminosilicate crystals, and lithium phosphate crystals, and is essential. The content of Li2O is 10% or more, preferably 15% or more, more preferably 20% or more, and even more preferably 25% or more. On the other hand, in order to maintain chemical durability, the content of Li2O is preferably 50% or less, more preferably 45% or less, and even more preferably 40% or less.

[0078] Na2O is a component that improves the melting property of glass. Although Na2O is not essential, it is preferably 0.1% or more, more preferably 0.5% or more, even more preferably 1% or more, and particularly preferably 2% or more. If the amount of Na2O is too much, lithium metasilicate crystals are difficult to precipitate or the chemical strengthening properties are reduced, so it is preferably 7% or less, more preferably 6% or less, and even more preferably 5% or less.

[0079] K2O is a component that lowers the melting temperature of glass like Na2O, and may be contained. When K2O is contained, the content is preferably 0.1% or more, more preferably 0.5% or more, even more preferably 1% or more, even more preferably 1.5% or more, and particularly preferably 2% or more. If the amount of K2O is too much, the chemical strengthening properties are reduced, so the content is preferably 5% or less, more preferably 4% or less, even more preferably 3% or less, and particularly preferably 2% or less.

[0080] The total content of Na2O and K2O (Na2O+K2O) is preferably 0.5% or more, more preferably 1% or more, and is preferably 7% or less, more preferably 6% or less, and even more preferably 5% or less.

[0081] P2O5 is not essential in the case of crystallized glass containing lithium silicate or lithium aluminosilicate, but it may be contained since it has the effect of promoting phase separation of glass and promoting crystallization. In addition, it is an essential component in the case of crystallized glass containing lithium phosphate crystals. When P2O5 is contained, the content is preferably 0.5% or more, more preferably 1% or more, and even more preferably 1.5% or more. On the other hand, if the content of P2O5 is too high, phase separation occurs easily during melting, and acid resistance is significantly reduced. The content of P2O5 is preferably 5% or less, more preferably 4% or less, and even more preferably 3% or less.

[0082] ZrO2 is a component that can form crystal nuclei during crystallization treatment, and may be contained. The content of ZrO2 is preferably 1% or more, more preferably 2% or more, even more preferably 2.5% or more, and particularly preferably 3% or more. On the other hand, in order to suppress devitrification during melting, the content of ZrO2 is preferably 6% or less, more preferably 5.5% or less, and even more preferably 5% or less.

[0083] TiO2 is a component that can form crystal nuclei during crystallization treatment, and may be contained. TiO2 is not essential, but if it is contained, it is preferably 0.5% or more, more preferably 1% or more, even more preferably 2% or more, particularly preferably 3% or more, and most preferably 4% or more. On the other hand, in order to suppress devitrification during melting, the content of TiO2 is preferably 10% or less, more preferably 8% or less, and even more preferably 6% or less.

[0084] SnO2 has the effect of promoting the formation of crystal nuclei and may be contained. SnO2 is not essential, but when it is contained, it is preferably 0.5% or more, more preferably 1% or more, even more preferably 1.5% or more, and particularly preferably 2% or more. On the other hand, in order to suppress devitrification during melting, the content of SnO2 is preferably 6% or less, more preferably 5% or less, even more preferably 4% or less, and particularly preferably 3% or less.

[0085] Y2O3 is a component that makes it difficult for chemically strengthened glass to scatter fragments when broken, and may be contained. The content of Y2O3 is preferably 1% or more, more preferably 1.5% or more, even more preferably 2% or more, particularly preferably 2.5% or more, and extremely preferably 3% or more. On the other hand, in order to suppress devitrification during melting, the content of Y2O3 is preferably 5% or less, more preferably 4% or less.

[0086] Although not essential, B2O3 is a component that improves the chipping resistance of the chemically strengthened glass or the chemically strengthened glass and improves the melting property, and may be contained. When B2O3 is contained, the content is preferably 0.5% or more in order to improve the melting property, more preferably 1% or more, and even more preferably 2% or more. On the other hand, if the content of B2O3 exceeds 5%, striae are generated during melting and the quality of the chemically strengthened glass is likely to deteriorate, so 5% or less is preferable. The content of B2O3 is more preferably 4% or less, even more preferably 3% or less, and particularly preferably 2% or less.

[0087] BaO, SrO, MgO, CaO, and ZnO are components that improve the melting property of glass and may be contained. When these components are contained, the total of BaO, SrO, MgO, CaO, and ZnO (BaO+SrO+MgO+CaO+ZnO) is preferably 0.5% or more, more preferably 1% or more, even more preferably 1.5% or more, and particularly preferably 2% or more. On the other hand, since the ion exchange rate decreases, the content of BaO+SrO+MgO+CaO+ZnO is preferably 8% or less, more preferably 6% or less, even more preferably 5% or less, and particularly preferably 4% or less.

[0088] Among these, BaO, SrO, and ZnO may be contained to improve the refractive index of the residual glass and bring it closer to the precipitated crystal phase, thereby improving the transmittance of the crystallized glass and reducing the haze value. In this case, the total content of BaO+SrO+ZnO is preferably 0.3% or more, more preferably 0.5% or more, even more preferably 0.7% or more, and particularly preferably 1% or more. On the other hand, these components may reduce the ion exchange rate. In order to improve the chemical strengthening properties, BaO+SrO+ZnO is preferably 2.5% or less, more preferably 2% or less, even more preferably 1.7% or less, and particularly preferably 1.5% or less.

[0089] CeO2 may also be contained. CeO2 has the effect of oxidizing glass and may suppress coloring. When CeO2 is contained, the content is preferably 0.03% or more, more preferably 0.05% or more, and even more preferably 0.07% or more. When CeO2 is used as an oxidizing agent, the content of CeO2 is preferably 1.5% or less, more preferably 1.0% or less, in order to increase transparency.

[0090] When the tempered glass is colored, a coloring component may be added to the glass as long as it does not impede the achievement of the desired chemical strengthening properties. Suitable examples of the coloring component include Co3O4, MnO2, Fe2O3, NiO, CuO, Cr2O3, V2O5, Bi2O3, SeO2, Er2O3, and Nd2O3.

[0091] The total content of coloring components is preferably within the range of 1% or less. If it is desired to increase the visible light transmittance of the glass, it is preferable that these components are substantially not contained.

[0092] In addition, SO3, chlorides, fluorides, etc. may be appropriately contained as a fining agent when melting the glass. It is preferable that As2O3 is not contained. When Sb2O3 is contained, it is preferably 0.3% or less, more preferably 0.1% or less, and most preferably not contained.

[0093] Hereinafter, the mol% of a certain component A is referred to as C-A. The present invention is applicable to any crystals precipitated as a crystal phase, but in order to obtain a more transparent crystallized glass, the mol% ratio of Li2O to SiO2 C-Li2O / C-SiO2 is preferably 0.4 or more, more preferably 0.45 or more, and even more preferably 0.5 or more. It is also preferably 0.85 or less, more preferably 0.80 or less, and even more preferably 0.75 or less. This makes it easier to obtain lithium metasilicate, and as a result, a highly transparent crystallized glass can be obtained by controlling the particle size.

[0094] Also, C-Li2O / C-Na2O is preferably 4 or more, more preferably 8 or more, and even more preferably 12 or more. Also, it is preferably 30 or less, more preferably 28 or less, and even more preferably 25 or less. This makes it easier to obtain a stress profile in which the surface stress is relaxed while sufficient compressive stress due to chemical strengthening is applied.

[0095] 2. Manufacturing method of chemically strengthened glass One embodiment of the method for producing chemically strengthened glass of the present invention includes, for example, a method in which the above-mentioned crystallizable amorphous glass is heat-treated to obtain crystallized glass, and the obtained crystallized glass is chemically strengthened to produce the glass.

[0096] <Production of amorphous glass> The amorphous glass can be produced, for example, by the following method. Note that the production method described below is an example of the case of producing a plate-shaped chemically strengthened glass.

[0097] Glass raw materials are mixed so as to obtain glass of a desired composition, and are heated and melted in a glass melting furnace. The molten glass is then homogenized by bubbling, stirring, adding a clarifier, etc., and formed into a glass plate of a predetermined thickness by a known forming method, and slowly cooled. Alternatively, the molten glass may be formed into a block shape, slowly cooled, and then cut into a plate shape.

[0098] Examples of the forming method of plate glass include the float method, the press method, the fusion method, and the down-draw method. In particular, when producing a large glass plate, the float method is preferred. In addition, continuous forming methods other than the float method, such as the fusion method and the down-draw method, are also preferred.

[0099] <Crystallization treatment> When the lithium aluminosilicate glass in the present invention is crystallized glass, the crystallized glass can be obtained by heat-treating the crystallizable amorphous glass obtained by the above procedure.

[0100] The heat treatment is preferably a two-stage heat treatment in which the temperature is raised from room temperature to a first treatment temperature and held for a certain period of time, and then the temperature is held for a certain period of time at a second treatment temperature that is higher than the first treatment temperature.

[0101] In the case of two-stage heat treatment, the first treatment temperature is preferably in a temperature range where the crystal nucleation rate is high in the glass composition, and the second treatment temperature is preferably in a temperature range where the crystal growth rate is high in the glass composition. In addition, the holding time at the first treatment temperature is preferably long so that a sufficient number of crystal nuclei are generated. By generating a large number of crystal nuclei, the size of each crystal becomes small, and a highly transparent crystallized glass is obtained.

[0102] The first treatment temperature is, for example, 450° C. to 700° C., and the second treatment temperature is, for example, 600° C. to 800° C. After being held at the first treatment temperature for 1 to 6 hours, the second treatment temperature is held for 1 to 6 hours.

[0103] The crystallized glass obtained by the above procedure is ground and polished as necessary to form a crystallized glass plate. When the crystallized glass plate is cut into a predetermined shape and size or chamfered, it is preferable to perform the cutting or chamfering before the chemical strengthening treatment, because a compressive stress layer is formed on the end surface by the subsequent chemical strengthening treatment.

[0104] <Production of chemically strengthened glass> The chemically strengthened glass of the present invention is produced by chemically strengthening a lithium-containing glass. The lithium-containing glass preferably has the above-mentioned composition.

[0105] The lithium-containing glass can be produced by a conventional method. For example, the raw materials of the glass components are mixed and heated and melted in a glass melting furnace. The glass is then homogenized by a known method, formed into a desired shape such as a glass plate, and slowly cooled.

[0106] Examples of glass forming methods include the float method, the press method, the fusion method, and the down-draw method. In particular, the float method, which is suitable for mass production, is preferred. Continuous forming methods other than the float method, such as the fusion method and the down-draw method, are also preferred.

[0107] Thereafter, the molded glass is ground and polished as necessary to form a glass substrate. When the glass substrate is cut into a predetermined shape and size or chamfered, it is preferable to cut or chamfer the glass substrate before carrying out the chemical strengthening treatment described later, since a compressive stress layer is formed on the end surface by the subsequent chemical strengthening treatment.

[0108] In the method for producing chemically strengthened glass of the present invention, the chemical strengthening is preferably performed using a strengthening salt containing sodium and having a potassium content of less than 5 mass%. In the method for producing chemically strengthened glass of the present invention, the chemical strengthening treatment may be performed in two or more stages, but one-stage strengthening is preferred in order to increase productivity.

[0109] Appropriate conditions for the chemical strengthening treatment may be selected in consideration of the composition (characteristics) of the glass, the type of molten salt, and the desired chemical strengthening characteristics. The chemical strengthening treatment is carried out, for example, by immersing the glass plate in a molten salt such as sodium nitrate heated to 360 to 600° C. for 0.1 to 500 hours. The heating temperature of the molten salt is preferably 375 to 500° C., and the immersion time of the glass plate in the molten salt is preferably 0.3 to 200 hours.

[0110] The reinforcing salt used in the method for producing chemically strengthened glass of the present invention is a reinforcing salt containing sodium and having a potassium content of less than 5 mass%. The potassium content in the reinforcing salt is preferably 2 mass% or less, and more preferably substantially free. "Substantially free of potassium" means that potassium is not contained at all, or that potassium may be contained as an impurity inevitably mixed in during production.

[0111] Examples of the reinforcing salt include nitrates, sulfates, carbonates, and chlorides. Examples of the nitrates include lithium nitrate and sodium nitrate. Examples of the sulfates include lithium sulfate and sodium sulfate. Examples of the carbonates include lithium carbonate and sodium carbonate. Examples of the chlorides include lithium chloride, sodium chloride, cesium chloride, and silver chloride. These reinforcing salts may be used alone or in combination. EXAMPLES

[0112] The present invention will be described below using examples, but the present invention is not limited thereto. In addition, for each measurement result in the table, a blank indicates that the measurement was not performed. Examples 1 to 4 are examples, and Example 5 is a comparative example.

[0113] [Preparation and evaluation of amorphous glass] Glass raw materials were mixed to obtain the glass composition shown in Table 1 in terms of oxide-based mole percentage, and melted and polished glass plates were produced. As glass raw materials, general glass raw materials such as oxides, hydroxides, and carbonates were appropriately selected and weighed out to give 900 g of glass. The mixed glass raw materials were placed in a platinum crucible, melted at 1700°C, and degassed. The glass was poured onto a carbon board to obtain a glass block. A portion of the obtained block was used to evaluate the results, which are shown in Table 1. Blanks in the table indicate that no evaluation was performed.

[0114] [Preparation and evaluation of glass-ceramics] The obtained glass block was processed to 50 mm x 50 mm x 1.5 mm, and then heat-treated under the conditions shown in Table 1 to obtain crystallized glass. In the crystallization condition column in the table, the upper row indicates the nucleation treatment conditions, and the lower row indicates the crystal growth treatment conditions. For example, if 550-2 is written in the upper row and 730-2 is written in the lower row, it means that the glass was held at 550°C for 2 hours, and then at 730°C for 2 hours. Using a portion of the obtained crystallized glass, it was confirmed by powder X-ray diffraction that it contained lithium metasilicate.

[0115] The obtained crystallized glass was processed and mirror-polished to obtain a crystallized glass plate with a thickness t of 0.7 mm. A rod-shaped sample was also prepared to measure the thermal expansion coefficient. A portion of the remaining crystallized glass was crushed and used to analyze the precipitated crystals. The evaluation results of the crystallized glass are shown in Table 1. Blanks in the table indicate that no evaluation was performed.

[0116] [Preparation and evaluation of chemically strengthened glass] The obtained crystallized glass was subjected to a chemical strengthening treatment under the strengthening conditions shown in Table 2 to obtain chemically strengthened glass. Examples 1 to 4 are working examples, and Example 5 is a comparative example. In Table 1, "Na100%" indicates a molten salt of 100% sodium nitrate, "Na99.7%Li0.3%" indicates a molten salt of 99.7 wt% sodium nitrate mixed with 0.3 wt% lithium nitrate, and "K100%" indicates a molten salt of 100% potassium nitrate. The results of evaluation of the obtained chemically strengthened glass are shown in Table 2. Blanks in the table indicate no evaluation.

[0117] [Evaluation method] (glass transition temperature Tg, thermal expansion coefficient) Based on JIS R1618:2002, a thermal expansion curve was obtained using a thermal dilatometer (TD5000SA manufactured by Bruker AXS) at a heating rate of 10°C / min, and the glass transition point Tg [unit: °C] and the thermal expansion coefficient were calculated from the obtained thermal expansion curve.

[0118] (specific gravity) Measured by Archimedes method.

[0119] (Young's Modulus) The Young's modulus was measured by an ultrasonic method.

[0120] (Refractive Index) The sample was mirror-polished to a size of 15 mm x 15 mm x 0.8 mm, and the refractive index was measured by the V-block method using a precision refractometer KPR-2000 (manufactured by Shimadzu Devices Manufacturing Co., Ltd.).

[0121] (Vickers hardness) The Vickers hardness was measured in accordance with the test method specified in JIS-Z-2244 (2009) (ISO6507-1, ISO6507-4, ASTM-E-384) using a Shimadzu Vickers hardness tester (MICRO HARDNESS TESTER HMV-2) under normal temperature and humidity conditions (in this case, the room temperature was maintained at 25°C and the humidity was maintained at 60% RH). Measurements were taken at 10 points per sample, and the average of the measurements was taken as the Vickers hardness of the prototype. The Vickers indenter was pressed with a load of 0.98N for 15 seconds.

[0122] (Fracture toughness value) The fracture toughness value was measured by the DCDC method using a sample measuring 6.5 mm x 6.5 mm x 65 mm, with a 2 mm diameter through hole drilled in the 65 mm x 6.5 mm surface of the sample.

[0123] (Total visible light transmittance) The transmittance of the crystallized glass plate at wavelengths of 380 to 780 nm was measured using a spectrophotometer (PerkinElmer; LAMBDA950) with an integrating sphere unit (150 mm InGaAs Int. Specter) as a detector. The glass plate was placed in close contact with the integrating sphere during the measurement, and measurements were made including diffuse transmitted light. The average transmittance, which is the arithmetic mean value of the transmittance, was taken as the visible light transmittance [unit: %].

[0124] (Haze value) The haze value (unit: %) under light source C was measured using a haze meter (HZ-V3 manufactured by Suga Test Instruments) in accordance with the method specified in JIS K 7136 (2000).

[0125] (X-ray diffraction: precipitated crystals and crystallization rate) The precipitated crystals were identified by powder X-ray diffraction under the following conditions. The crystallization rate was calculated from the obtained diffraction intensity by the Rietveld method. Measurement equipment: Rigaku SmartLab X-ray used: CuKα ray Measurement range: 2θ=10°~80° Speed: 10° / min Step: 0.02°

[0126] The detected crystals are shown in the column for main crystals in Table 1. In the table, LS stands for lithium metasilicate.

[0127] (Stress Profile) First, the stress profile was measured using a measuring instrument SLP-2000 manufactured by Orihara Seisakusho, and the stress characteristics (compressive stress value at a depth of 50 μm, CS 50[unit: MPa], CT [unit: MPa], and the depth DOL [unit: μm] at which the compressive stress value becomes zero were obtained. For the obtained stress profile, the gradient (MPa / μm) of the stress curve in the thickness range of DOL ± 10 μm and the gradient (MPa / μm) of the stress curve in the thickness range of the plate thickness center ± 0.20 × t (μm) were calculated every 2 μm, and the maximum absolute value was obtained. In addition, the compressive stress value CS0 [unit: MPa] of the glass surface and the position (μm) of the inflection point of the compressive stress curve between the main surface and DOL were analyzed by a method using a birefringence imaging system Abrio-IM manufactured by Tokyo Instruments Co., Ltd. and a thin-sectioned sample. The results are shown in Table 2. The stress profile of Example 1 is shown in Figure 3. In the method using Abrio-IM and the thinned sample, the thickness of the thinned plate was set to 0.5 mm. In order to correct the stress fluctuation caused by thinning, the obtained stress profile was multiplied by 1 / (1-ν), where ν is the Poisson's ratio of glass.

[0128] (Ion concentration by EPMA) The ion concentration on the glass surface was measured using an EPMA (JEOL JXA-8500F). After chemical strengthening, the sample was embedded in resin and mirror-polished so that the cross section along the plate thickness direction was exposed. The position of the outermost surface was determined as the position where the signal intensity of Si, which is thought to have almost no change in content, was half that of the signal intensity at the plate thickness center, and the signal intensity at the plate thickness center was assumed to correspond to the glass composition before strengthening, and the ion concentration was calculated assuming that the concentration was proportional to the signal intensity. Table 2 shows the gradient of the obtained Na concentration curve in the plate thickness direction range of DOL ± 10 μm, and the presence or absence of an inflection point in the plate thickness direction range between the first main surface and the depth where the compressive stress value is 0. The signal intensity of the main ions in Example 1 is shown in Figure 4 (a), and the calculated Na ion concentration profile is shown in Figure 4 (b). In Figure 4 (b), the Na ion concentration at the plate thickness center is set to twice the Na2O concentration in the glass composition.

[0129] (Weather resistance test) The haze value was measured after leaving the specimen standing at 80% humidity and 80°C for 10 hours. The haze value does not change due to chemical strengthening treatment, but increases after leaving the specimen standing at 80% humidity and 80°C for 120 hours. The difference from the haze value before the test (i.e., |Haze value after test [%] - Haze value before test [%]|) is shown in Table 2 as [Haze change (%)].

[0130] (Number of crushed pieces) Using a Vickers testing machine, a Vickers indenter with a 90° tip angle was driven into the center of the test glass plate to break it, and the number of broken pieces was recorded as the number of pieces. (If the glass plate breaks into two, the number of broken pieces is 2.) If very fine pieces were generated, the number of pieces that did not pass through a 1 mm sieve was counted and recorded as the number of broken pieces. The test was started with a Vickers indenter impact load of 3 kgf. If the glass plate did not break, the impact load was increased by 1 kgf and the test was repeated until the glass plate broke. The number of fragments when the glass plate first broke was counted.

[0131] (Drop test) For the drop test, the obtained glass sample of 120 x 60 x 0.6 mmt was fitted into a structure whose mass and rigidity were adjusted to match the size of a typical smartphone currently in use, and then a mock smartphone was prepared and allowed to freely drop onto #180SiC sandpaper. The sample was dropped from a height of 5 cm. If the sample did not break, it was dropped from a height of 5 cm higher and dropped again, and this process was repeated until the sample broke. The average height at which the 10 samples first broke is shown in Table 1.

[0132] [Table 1]

[0133] [Table 2]

[0134] As shown in Table 2, Examples 1 to 4, which are working examples, have a Na concentration gradient and a stress gradient within the ranges specified by the present invention, and while containing 10 mol% or more of Li2O, have a stress profile similar to that of conventional lithium-free glass, and compared with the comparative example, fracture during scratching is suppressed and excellent strength and weather resistance are shown. Moreover, Examples 1 to 3 have an inflection point in the compressive stress curve in the thickness direction range between the position at a depth of 10 μm from the first main surface and the depth at which the compressive stress value is 0, and show higher strength than Example 4, in which the compressive stress curve does not include an inflection point in the range.

[0135] Although the present invention has been described in detail with reference to specific embodiments, it is apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. This application is based on a Japanese patent application (Patent Application No. 2019-118969) filed on June 26, 2019, and is incorporated by reference in its entirety. In addition, all references cited herein are incorporated in their entirety.

Claims

1. A first main surface, a second main surface opposite the first main surface, and an end portion in contact with the first main surface and the second main surface, When the compressive stress value inside the glass is expressed using the depth from the first main surface as a variable, A chemically strengthened glass that satisfies the following (1a) to (6a) and is a crystallized glass. (1a) In a thickness range of ±10 μm at a depth where the compressive stress value is 0, The gradient of the stress curve is -15 MPa / μm to -3 MPa / μm, and The gradient of the Na concentration curve defined below has an absolute value of 0.02 / μm to 0.12 / μm. Na concentration curve: A Na concentration curve obtained by converting the Na ion concentration profile in the plate thickness direction of the chemically strengthened glass measured by EPMA into an oxide-based molar percentage. (2a) The gradient of the Na concentration curve in the thickness direction range between the first principal surface and the depth at which the compressive stress value is 0 monotonically decreases. (3a) The thickness is 1 mm or less. (4a) Li in mole percentage based on oxide 2 O is 20 mol% or more and Na 2 The O content is 0.1 mol % or more. (5a) Young's modulus is 103 GPa or more. (6a) The visible light transmittance converted to a thickness of 0.7 mm is 85% or more.

2. The thickness is t (μm), and the average value of the gradient of the stress curve in the range in the thickness direction between the plate thickness center tc (μm) and (tc-0.20 × t) (μm) is 1 MPa / The chemically strengthened glass according to claim 1, having an absolute value of less than μm.

3. In the range in the plate thickness direction between the first main surface and the depth at which the compressive stress value is 0, The compressive stress curve measured using a birefringence imaging system Abrio-IM manufactured by Tokyo Instruments Inc. includes an inflection point, and The chemically strengthened glass according to claim 1 or 2, wherein the Na concentration curve does not include an inflection point.

4. 4. The chemically strengthened glass according to claim 3, wherein the compressive stress curve includes an inflection point in a range in the plate thickness direction between a position at a depth of 10 μm from the first main surface and a depth at which the compressive stress value is 0.

5. The chemically strengthened glass according to claim 4, wherein the crystallization rate of the crystallized glass is 10% or more.

6. The chemically strengthened glass according to claim 4 or 5, wherein the crystallized glass contains lithium metasilicate crystals.

7. The chemically strengthened glass according to any one of claims 4 to 6, wherein the haze value of transmitted light converted to a thickness of 0.7 mm measured by a method conforming to JIS K 7136 (2000) is 0.01 to 0.2%.

8. A ceramic substrate having a first main surface, a second main surface opposite to the first main surface, and an end portion contacting the first main surface and the second main surface, a thickness of 1 mm or less, and a mole percentage of Li based on oxides. 2 O is 20 mol% or more and Na 2 A method for producing chemically strengthened glass, comprising chemically strengthening glass containing 0.1 mol% or more of O and having a Young's modulus of 103 GPa or more, The chemical strengthening is a chemical strengthening using a strengthening salt containing sodium and having a potassium content of less than 5% by mass, The resulting chemically strengthened glass is a crystallized glass, When the compressive stress value inside the glass is expressed using the depth from the first main surface as a variable, A method for producing chemically strengthened glass that satisfies the following (1b) to (3b). (1b) In a thickness range of ±10 μm at a depth where the compressive stress value is 0, The gradient of the stress curve is -15 MPa / μm to -3 MPa / μm, and The gradient of the Na concentration curve defined below has an absolute value of 0.02 / μm to 0.12 / μm. Na concentration curve: A Na concentration curve obtained by converting the Na ion concentration profile in the plate thickness direction of the chemically strengthened glass measured by EPMA into an oxide-based molar percentage. (2b) The gradient of the Na concentration curve in the thickness direction range between the first principal surface and the depth at which the compressive stress value is 0 monotonically decreases. (3b) The visible light transmittance converted to a thickness of 0.7 mm is 85% or more.

9. The crystallized glass is In terms of mole percentage based on oxide, SiO 2 40 to 65% Al 2 O 3 を0~10%、 Li 2 Oを20~40%、 Na 2 Oを0.1~10%、 K 2 O 0.1 to 10%, The method for producing chemically strengthened glass according to claim 8, comprising:

10. The method for producing chemically strengthened glass according to claim 8 or 9, wherein the crystallized glass contains lithium metasilicate crystals.

Citation Information

Patent Citations

  • Inorganic composition article

    JP2008254984A

  • Chemically strengthened glass

    JP2013520388A

  • Glasses and glass-ceramics with metal oxide concentration gradients

    JP2017537862A

  • Chemical strengthened glass and method for producing the same

    JP2018131358A

  • High strength glass ceramic having lithium disilicate and β-spodumene structure

    JP2019081705A